Design and synthesis of 3, 5- hetero diesters of 4-deoxy quinic acid and their aphicidal activity against Acyrthosiphon pisum. (12th March 2021) - Li, Xiubin; Sivignon, Catherine; da Silva, Pedro; Rahbé, Yvan; Queneau, Yves; Moebs-Sanchez, Sylvie
Abstract: Four analogs of 3, 5-dicaffeoylquinic acid, including a new heterodiester of 4-deoxyquinic acid, were found toxic against the pea aphid. Several 4-deoxy quinic analogs featuring two different hydroxyl cinnamoyl moieties in position 3 and 5 were prepared for the first time and carefully analysed. Through an assay on pea aphid nymphs, interesting indications on the structure-aphicidal activity relationships and higher levels of toxicity were observed for four compounds related to the reference natural compound. Graphical abstract: Image 1 Highlights: Analogs of chlorogenic acids featuring different and various hydroxyl cinnamoyl groups in 3 and 5 positions. Four compounds were found to exhibit higher aphicidal activities than natural 3, 5-di- O -caffeoylquinic acid. Both acetylated 3- O -feruloyl-5- O -caffeoyl and 3- O -caffeoyl-5- O -coumaroyl compounds were active. Observation of an interesting structure-activity difference for two regioisomers.